THE ROLE OF GOLD AND SILVER IN THE ISLAMIC MONETARY SYSTEM - Asty Amanda; Elvira Mey Roza; Tongku Harapan Martua; Mahmud Yunus (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
The Islamic monetary system possesses distinct characteristics that differentiate it from conventional systems, particularly in its reliance on real commodities as a medium of exchange and store of value. Gold (dinar) and silver (dirham) have historically served as the primary instruments in the Islamic monetary framework, from the time of Prophet Muhammad (PBUH) through the era of the Rightly Guided Caliphs. This article explores the strategic role of gold and silver in maintaining economic stability, preventing inflation, and fostering a just financial system. Unlike fiat currencies, whose value is often influenced by debt and artificial monetary policies, gold and silver derive their worth from intrinsic value. This study employs a qualitative approach through literature review of classical and contemporary sources. The findings indicate that using gold and silver as currency offers resilience against global economic fluctuations, minimizes value volatility, and enhances trust in transactions. Reintroducing the dinar-dirham system is viewed as a potential solution to current monetary crises and global financial inequality, although several technical and structural challenges must be addressed before practical implementation can be realized.